(untitled) (Academia Journal of Medicine, 2021)
Background: Nephrotic syndrome has an incidence of three new cases per 100 000 each year in adults. Despite considerable advances in health care, glomerular disease constitutes one of the leading causes of renal failure resulting in considerable morbidity and mortality. In India, the histological type varies according to the demographic location, and treatment regime depends on the type of nephrotic syndrome. RDW is an inexpensive blood test and there are several studies that show a close relationship between RDW values and inflammatory activity. Our aim in this study is to test the predictive value of RDW in determining treatment response to therapy in adult nephrotic syndrome. Subjects and Methods: Newly diagnosed primary adult nephrotic syndrome patients admitted to Victoria hospital and hospitals attached to Bangalore Medical College and Research institute (BMCRI), between May 2018 to September 2020 were chosen for the study. The patients were recruited as per inclusion criteria and demographic profile, medical history, comorbidities, detailed physical examination and lab investigation such as serum creatinine, and 24 hour urine protein were recorded in the study performa . Patients who have nephrotic range proteinuria (> 3.5 gm/24 hrs) with sonographically normal sized kidneys were subjected to renal biopsy to identify the etiopathology. Following this appropriate treatment was iniated and the patients were followed up for the duration of the study. Results: Our study included 39 patients with nephrotic syndrome were treated in hospitals attached to BMCRI. Of these patients, males constituted 61.5% and females 38.5%. 53.8% of cases occurred in third decade of life. The commonest presenting symptom among these patients was pedal edema. MGN was the most common histological variant followed by IgA nephropathy and MCGN. Mean RDW values among those who were resistant to treatment was 18.58+/- 0.62 and 13.23+/- 0.74 among those who responded to treatment. Difference in RDW between the two groups was found to be statistically significant showing that high RDW values may be associated with poor treatment response. Conclusion: In our study high RDW values were found to be associated with high rates of treatment resistance. These findings suggest that RDW may be used as a useful biomarker to predict treatment response in nephrotic syndrome patients.